ANALISIS HASIL BELAJAR DAN MASA STUDI MAHASISWA CALON GURU MATEMATIKA - Ibrahim Ibrahim (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
The main objective of this research is to analyze the correlation between learning outcomes in the first year, the final results of study and the period of study of students. The research method used is quantitative (descriptive-associative) method. This research is an ex-post research. The sample of this study was 317 students of the Mathematics Education Study Program, Faculty of Science and Technology from 2006 to 2010. Data analysis techniques used in this study were the average difference test and the correlation test. Research data were collected using documentation. Learning outcomes data in the first year and final study data using IPK data, and study period data using the number of semesters taken by students. This study concludes that the learning outcomes in the first year and the final results of the study of mathematics teacher candidates at UIN Sunan Kalijaga are more than 3.00, but the study period is more than 8 semesters. In addition, this study also concluded that there was a positive correlation between learning outcomes in the first year and the final results of student studies, but there was a negative correlation between learning outcomes in the first year and the period of study of students and between the final results of study and study period of students.